Autoantibodies against TYMS and PDLIM1 proteins detected as circulatory signatures in Indian breast cancer patients. Issue 5 (May 2016) - Gupta, Prachi; Suman, Shankar; Mishra, Manisha; Mishra, Sanjay; Srivastava, Nidhi; Kumar, Vijay; Singh, Pradhyumna Kumar; Shukla, Yogeshwer
Abstract : Purpose: Breast cancer (BC) is the most common invasive cancer in women worldwide. Autoantibodies (AAbs) to tumor‐associated antigens (TAAs) have a great potential for the development of diagnostic biomarkers in cancer. This study was performed to identify AAbs and cognate TAAs that may improve detection of this deadly disease. Experimental design: Serological proteome analysis of plasma samples of BC patients ( N = 30) and healthy controls ( N = 30) was performed to identify TAAs. Expressions of selected TAAs were also determined in breast tumor tissues ( N = 10) by immunohistochemistry. An independent validation cohort ( N = 124) was tested to determine diagnostic accuracy of selected AAbs titer by ELISA. Results: Thymidylate synthase (TYMS) and C‐terminal LIM domain protein 1 (PDLIM1) were found to react more specifically with plasma samples of BC patients. Both TAAs were also found to be significantly over expressed ( p < 0.001) in breast tumor tissues compared to adjacent normal tissues. TYMS AAbs response was positively correlated ( r = 0.778, p < 0.008) with TYMS overexpression in BC tissues. TYMS and PDLIM1 AAbs titers discriminated BC from controls with a sensitivity/specificity of 57.81%/95% and 73.44%/58.33%, respectively. Conclusion and clinical relevance: High titers of both TYMS and PDLIM1 AAbs were significantly more prevalent in BC cases than controls. Our data recommends further investigations for evaluating their potential for BC detection.